Supplementary MovieS2a from Immunotherapeutic Targeting and PET Imaging of DLL3 in Small-Cell Neuroendocrine Prostate Cancer - Jonathan Chou (14957015) (2025)
Supplemental Movies 2a-2c: 22Rv1-NuclightGreen and SHP-77-NuclightRed mixed population co-cultures. Time-lapse movies of 22Rv1 cells (labeled with NuclightGreen) and SHP-77 cells (labeled with NuclightRed) co-cultured with T cells. Both the 22Rv1 and SHP-77 cells were plated at equal densities and treated with either NT control BiTE®, AMG 757, or the PSMA-targeting HLE BiTE, AMG 160. T cells were added to each well at an E:T ratio of 10:1. Images were captured every 4 hours at 4x magnification for 5 days. a.22Rv1, SHP-77, and T cells co-cultured with NT control BiTE®. b.22Rv1, SHP-77, and T cells co-cultured with AMG 757. c.22Rv1, SHP-77, and T cells co-cultured with AMG 160.